Work-Life Balance: Conceptualization, Antecedents and Consequences - Wulansari, Nury Ariani; Harsono, Mugi (Universitas Negeri Semarang, 2022)
The notion of work-life balance (WLB), which integrates two primary dimensions, engagement in work and non-work life, and minimum conflict between social role in one’s work and in one’s life has evolved from a review of much of the literature in previous research. Beside that, the identification of antecedent variables from both individual and organizational levels that could affect WLB and explained their influence on WLB are also examined in this study. To fully comprehend the differences in the factors that are able to influence WLB and are affected on WLB, identification of the consequent variables from the influence of WLB is also collected. From this identification process, future study path will be identified, and these directions will have consequences of leaving gaps for in-depth investigations and implications managerial policies related to WLB.